The role of geoinformatics techniques in predicting the urban growth of the city of Suez, Egypt, using the frequency ratio model. - Mohamed abdelzaher (The International Journal of Informatics, Media and Communication Technology, 2023)
Geoinformatics techniques help solve the most important real problems facing the city of Suez, perhaps the most prominent of which is the problem of population increase and the pressure on the current urban area. This problem can be solved by adopting a model that shows the scopes of the future urban expansion of the city according to many geographical criteria and factors such as natural, environmental, and economic factors, and therefore this technology is a means for decision-making through the results we obtain. In this context, the essence of spatial modeling lies in the management of geographical data through a cycle of steps to simulate the studied phenomenon. The study could apply the spatial modelling of the potential urban growth using Frequency Ratio, after applying the model, a map of spatial appropriateness has been concluded and consequently the model outputs have been evaluated from a geographical perspective.